Penerapan Pembelajaran Baca Tulis Al-Quran di SD Citra Al Madina - Harahap, Aziddin; Harahap, Hasmi Syahputra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The purpose of research to know teacher preparation in planning learning Al-quran read and write, described presentation weighting read write the Al-quran, to know of methods used teacher in learning Al-quran read and write, students in learning activity know read write Al-quran and supporting factors and read write an impediment to learning the Al-quran. While, as for research: a) material input for writer to add insight and knowledge in upgrading himself as a teacher, b) evaluation in the learning process for teachers of religion for the work done so far in learning al-quran read and write, c) Its input in order improve education material at SD Citra Al-Madina Padang. For answers to problems on the use writers field Research. To collect the data research, the use writers 80 survey to students and interview to teachers and headmaster at SD Citra Al-Madina. While the data the research is headmaster, teachers and adminitration. After data collected using is data tabulation. The conclusion that learning read and write Al-quran in Citra al Madina has been held well, then cause students to slow to be able to read the koran is teachers do not able to provide an homework, learning, no notes conclusion learning and students are not repeat the class in the house.